2020
DOI: 10.3390/nu12020380
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Postprandial Amino Acid and Gastrointestinal Hormone Responses to Beef Steak Cooked Using Different Methods: A Randomised Crossover Trial

Abstract: Cooking changes the texture and tenderness of red meat, which may influence its digestibility, circulatory amino acids (AA) and gastrointestinal (GI) hormonal responses in consumers. In a randomised crossover intervention, healthy males (n = 12) consumed a beef steak sandwich, in which the beef was cooked by either a pan-fried (PF) or sous-vide (SV) method. Plasma AA were measured by ultrahigh performance liquid chromatography (UPLC), while plasma GI hormones were measured using a flow cytometric multiplex arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…Sous vide processing renders meat juicier and more tender and at the same time, the technique improves the digestibility of meat, according to studies conducted on in vitro digestion [ 47 ]. However, in a study with young men, no differences were observed between the digestibility of sous vide cooked and fried meat in the pan [ 48 ]. Digestibility remains unknown in elderly adults.…”
Section: Processingmentioning
confidence: 99%
“…Sous vide processing renders meat juicier and more tender and at the same time, the technique improves the digestibility of meat, according to studies conducted on in vitro digestion [ 47 ]. However, in a study with young men, no differences were observed between the digestibility of sous vide cooked and fried meat in the pan [ 48 ]. Digestibility remains unknown in elderly adults.…”
Section: Processingmentioning
confidence: 99%
“…On the one hand, in the specific case of steam autoclave sterilization (121 • C for 20 min), it should be considered that this type of treatment could decrease the bioavailability of some amino acids due to protein denaturation [47], and this issue needs further investigation in future work, but the importance and the need to insert a safe food product that therefore respects the parameters of food safety in the food chain is a mandatory and essential prerequisite compared with the preservation of the nutritional and sensory characteristics. On the other hand, in human dietary habits proteins of animal origin are normally subjected to cooking treatment for the protection of consumer health and this treatment involves the reduction of amino acid bioavailability [48,49]. Further studies are necessary to investigate several aspects, from the possible presence of allergens to indirect transmission routes (fresh earthworm-farmed animal-human) since, as reported by Villate [50], some nematodes for whom earthworms are intermediate hosts represent a particular case in the contamination of livestock such as poultry, and this could represent a public health risk for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin, glucagon, GIP, GLP-1 and PYY were measured using MILLIPLEX ® MAP Human Metabolic Hormone Magnetic Bead Panel 96-Well Plate Assay (HMHEMAG-34K, Merck Millipore, Germany). Plasma AAs were measured using Ultra-High-Performance Liquid Chromatography assay with pre-column derivatisation using AccQ-Tag [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%